2007
DOI: 10.1111/j.1365-2672.2006.03075.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stabilizers on shelf-life of Epicoccum nigrum formulations and their relationship with biocontrol of postharvest brown rot by Monilinia of peaches

Abstract: Aim:  To find a formulation of Epicoccum nigrum conidia that maintains a high viability over time and which proves efficient to biocontrol peach rot caused by Monilinia spp. Methods and Results:  We tested the effect of stabilizers and desiccants on the shelf‐life of Epicoccum nigrum conidia. Conidial samples were dried for 40 min at 40°C in a fluidized bed‐dryer to obtain moisture contents <15%. The toxicity of additives was tested by assaying production of conidia in fermentations and germinability of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 30 publications
3
52
0
Order By: Relevance
“…This half-life figure is close to that obtained by Batta (2004) with T. harzianum conidia formulated in reverse emulsion (21 weeks). Several studies have found that formulated conidia remain viable for longer periods than non-formulated conidia (Guijarro et al, 2007;Larena et al, 2007;Wijesinghe et al, 2010Wijesinghe et al, , 2011. This prolonged viability is thought to be related to the specific role of the various ingredients of the formulation -in this case glucose and soybean oil.…”
Section: Discussionmentioning
confidence: 99%
“…This half-life figure is close to that obtained by Batta (2004) with T. harzianum conidia formulated in reverse emulsion (21 weeks). Several studies have found that formulated conidia remain viable for longer periods than non-formulated conidia (Guijarro et al, 2007;Larena et al, 2007;Wijesinghe et al, 2010Wijesinghe et al, , 2011. This prolonged viability is thought to be related to the specific role of the various ingredients of the formulation -in this case glucose and soybean oil.…”
Section: Discussionmentioning
confidence: 99%
“…1986; Madrigal et al. 1994) and postharvest brown rot caused by M. laxa and M. fructigena in laboratory and field commercial assays (Larena et al. 2005, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The estimated shelf life (DT50) of our hypovirulent Cp 4.2H strain preparation—2·5 months—was shorter than that of the Cp 4.2 virulent one and of other formulated biofungicides (Larena et al . ; Kobori et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…HPMC has the property of gelation, and unlike methylcellulose used as additive in other biopesticide formulations (Larena et al . ), its hydration is temperature dependent. We hypothesize that such behaviour could enable embedding of the micro‐organism and protection from desiccation, so that revitalization and progressive release of the fungus is easily achieved (Hari et al .…”
Section: Discussionmentioning
confidence: 99%